THE EFFECT OF ENTREPRENEURSHIP EDUCATION, AND SOCIAL ENVIRONMENT ON ENTREPRENEURIAL INTEREST WITH SELF-EFFICACY AS A MEDIATING VARIABLE - Brahmatiyo, Dodyk; Muwarni, F. Danardana; Kusdiyanti, Heny (International Journal of Business, Law, and Education, 2023)
Entrepreneurial interest is still quite low in Indonesia because it is known that until now the number of entrepreneurs has not been able to reach the ideal number, SMK as a vocational school must always develop its quality to realize high-quality graduates in answering the needs of the industrial world and creating new entrepreneurs. This study uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the hypotheses given. This study uses Google Forms for data collection on students of the Tourism Business Department of SMKN 1 Trowulan in Mojokerto Regency. Respondents in this study were 184 student respondents. The results showed that the Social Environment could not explain Self-efficacy or Entrepreneurial Interest. However, the Entrepreneurship Education variable can explain Self-efficacy and Entrepreneurial Interest. Furthermore, Entrepreneurship Education will have more influence on Entrepreneurial Interest, if strengthened by Self Efficacy as a mediator variable. The Social Environment will not have a greater influence on the Interest in Entrepreneurship, although strengthened with Self-efficacy as a mediator variable